The Influence of Organizational Culture on Employee Performance Mediated by Job Satisfaction and Employee Commitment - Bintang Bagaskara Korda; Riani Rachmawati (LPPM Universitas Terbuka, 2022)
Purpose – The study aimed to analyze the influence of organizational culture on employee performance mediated by job satisfaction and employee commitment. Methodology – A quantitative approach was used on 167 employees with a minimum of one year of experience working in a coating company. The sample size was the population of the industry. Furthermore, the data analysis was carried out using the Partial Least Square Structural Equation Modelling (PLS-SEM). Findings – This study found that organizational culture influences and improves employee performance. It also affects organizational commitment and job satisfaction, which mediate the culture to improve employee performance. Moreover, employee performance could be improved by increasing job satisfaction and commitment. Satisfaction also increases and affects employee commitment. Originality – This is the first study to investigate the influence of organizational culture on employee performance. It analyzed the relationship of job satisfaction, employee commitment, and performance and used a mediation variable to expand the theory in previous studies. This study also complements the relationship of variables in the organization for different service industries.